Clinical Outcomes of Posterior Versus Anterior Circulation Infarction With Low National Institutes of Health Stroke Scale Scores. Issue 1 (January 2017) - Kim, Joon-Tae; Park, Man-Seok; Choi, Kang-Ho; Kim, Beom Joon; Han, Moon-Ku; Park, Tai Hwan; Park, Sang-Soon; Lee, Kyung Bok; Lee, Byung-Chul; Yu, Kyung-Ho; Oh, Mi Sun; Cha, Jae Kwan; et al.
Abstract : Background and Purpose—: We compared baseline characteristics and outcomes at 3 months between patients with minor anterior circulation infarction (ACI) versus minor posterior circulation infarction (PCI), including the influence of large vessel disease on outcomes. Methods—: This study is an analysis of a prospective multicenter registry database in South Korea. Eligibility criteria were patients with ischemic stroke admitted within 7 days of stroke onset, lesions in either anterior or posterior circulation, and National Institutes of Health Stroke Scale score of ⩽4 at baseline. Patients were divided into 4 groups for further analysis: minor ACI with and without internal carotid artery/middle cerebral artery large vessel disease and minor PCI with and without vertebrobasilar large vessel disease. Results—: A total of 7178 patients (65.2±12.6 years) were analyzed in this study, and 2233 patients (31.1%) had disability (modified Rankin Scale score 2–6) at 3 months. Disability was 32.3% in minor PCI and 30.3% in minor ACI ( P =0.07), and death was 1.3% and 1.5%, respectively ( P =0.82). In a multivariable logistic regression analysis, minor PCI was significantly associated with disability at 3 months when compared with minor ACI (odds ratio, 1.23; 95% confidence interval, 1.09–1.37; P <0.001). In pairwise comparisons, minor PCI with vertebrobasilar large vessel disease was independently associated with disability at 3 months, compared with the other 3 groups. Conclusions—: Our study showed that minor PCI exhibited more frequent disability at 3 months than minor ACI. Especially, the presence of vertebrobasilar large vessel disease in minor PCI had a substantially higher risk of disability. Our results suggest that minor PCI with vertebrobasilar large vessel disease could require more meticulous care and are important targets for further study. Abstract : Supplemental Digital Content is available in the text.